Pendidikan Pesantren sebagai Ujung Tombak Pendidikan Nasional - Muhammad Nasrul Waton (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2017)
In the history of life, education is a most essential requirement for the survival of mankind. Role-education in addition to functioning in developing creativity and productivity, also plays a major role in efforts to develop morality and the planting of values, both human values and divine values. Pesantren is an educational institution that has a long and unique history. Historically, pesantren has included the earliest Islamic education and still survives to this day. Of the many types of boarding schools, in conducting education and teaching for students, in general can be grouped into two forms of pesantren: (1) Pesantren Salafiyah (2) Pesantren Khalafiyah. Education, as set forth in RI Law no. 20 Year 2003 Article 1 paragraph 1, is a conscious and planned effort to create an atmosphere of learning and learning process so that learners actively develop their potential to have spiritual strength, self-control, personality, intelligence, noble character, as well as the skills needed by him or her, society, nation and state. Indonesia national education system is based on the culture of the nation of Indonesia and based on Pancasila and the 1945 Constitution as a crystallization of the values of life of the Indonesian nation.